ANALYSIS OF THE INFLUENCE OF THE USE OF RECRUITMENT, SELECTION, AND JOB PLACEMENT SYSTEMS ON EMPLOYEE PERFORMANCE PT KAI DAOP 9 JEMBER - Permatasari, Desta Intan; Satoto, Eko Budi; Sumowo, Seno (Univesitas Muhammadiyah Tangerang, 2025)
Employee performance at PT. KAI Daop 9 Jember is still not optimal. This can be caused by several factors, one of which is recruitment, selection and job placement which have not been optimal. This research aims to analyze the influence of recruitment, selection and job placement on employee performance at PT.KAI Daop 9 Jember. This research uses quantitative methods with a survey approach. Data was collected through questionnaires distributed to 283 employees of PT. KAI Daop 9 Jember. The data analysis technique used is multiple linear regression. The research results show that recruitment has a significant effect on the performance of PT.KAI Daop 9 Jember employees, selection has a significant effect on the performance of PT.KAI Daop 9 Jember employees, and work placement has a significant effect on the performance of PT.KAI Daop 9 Jember employees.